2019
DOI: 10.1016/j.esxm.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Bondage-Discipline, Dominance-Submission and Sadomasochism (BDSM) From an Integrative Biopsychosocial Perspective: A Systematic Review

Abstract: Introduction BDSM (bondage and discipline, dominance and submission, and sadism and masochism) increasingly receives attention from the scientific community. Where earlier research efforts mainly focused on epidemiologic characteristics, psychological and biologic factors driving BDSM preferences have recently gained interest as well. Aim To bring together all the existing scientific literature on BDSM from a biopsychosocial perspective. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 103 publications
(183 reference statements)
0
34
1
Order By: Relevance
“…Moreover, it is acknowledged that other types of sexual behavior, such as “kink” and bondage, discipline, dominance and submission, and sadomasochism (BDSM), may be related to engagement in sexual risk in some populations ( McGregor, 2015 ). However, to the best of our knowledge, evidence that these behaviors are prevalent in university students is limited ( De Neef et al, 2019 ). Thus, it might be sensible to conceptualise them as correlates of sexual risk behaviors, rather than constituting sexual risk behaviors per se, in university students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is acknowledged that other types of sexual behavior, such as “kink” and bondage, discipline, dominance and submission, and sadomasochism (BDSM), may be related to engagement in sexual risk in some populations ( McGregor, 2015 ). However, to the best of our knowledge, evidence that these behaviors are prevalent in university students is limited ( De Neef et al, 2019 ). Thus, it might be sensible to conceptualise them as correlates of sexual risk behaviors, rather than constituting sexual risk behaviors per se, in university students.…”
Section: Introductionmentioning
confidence: 99%
“…They found that both men and women were equally satisfied with sexual encounters in both BDSM and non-BDSM contexts, and that men experienced less distress about sexual dysfunctions in a BDSM context than in non-BDSM contexts; for women, their level of distress about sexual dysfunctions did not differ between the BDSM versus non-BDSM context. De Neef et al (2019) also refer to unpublished results in their studies of BDSM practitioners who use FetLife (a popular social media website for kinky people), and found that 70% of their 363 respondents regularly or always combined BDSM play with sex, whereas 7% never combined sex and BDSM. Moser and Levitt (1987) asked specifically whether sadism and masochism (SM) activities were less satisfying or more satisfying than "straight" sex.…”
Section: Interaction Between Sex and Kinkmentioning
confidence: 99%
“…As an umbrella term, BDSM encompasses a wide range of activities and relationship styles (De Neef et al, 2019). Many definitions of BDSM have been presented within the academic literature as well as the community literature.…”
Section: Bdsm Terminology and Rolesmentioning
confidence: 99%